2014
DOI: 10.1002/2013jg002494
|View full text |Cite
|
Sign up to set email alerts
|

Rates and radiocarbon content of summer ecosystem respiration in response to long‐term deeper snow in the High Arctic of NW Greenland

Abstract: The amount and timing of snow cover control the cycling of carbon (C), water, and energy in arctic ecosystems. The implications of changing snow cover for regional C budgets, biogeochemistry, hydrology, and albedo due to climate change are rudimentary, especially for the High Arctic. In a polar semidesert of NW Greenland, we used a~10 year old snow manipulation experiment to quantify how deeper snow affects magnitude, seasonality, and 14 C content of summer C emissions. We monitored ecosystem respiration (R ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 118 publications
6
27
0
Order By: Relevance
“…This suggests that in our study the interaction between OTU richness and potential species abundance likely are habitat‐specific, and are in agreement with studies that addressed species‐species interactions (Kennedy et al ., ; Simard et al ., ; Fransson et al ., ). Collectively, our findings reflect the complexity of arctic tundra responses to predicted changes in summer and winter climate and the need to undertake comparative studies that include multiple ecosystem types even at reduced spatial scales (Welker et al ., ; Walker et al ., ; Sullivan et al ., ,b; Rogers et al ., ; Christensen et al ., ; Leffler & Welker, ; Sharp et al ., ; Lupascu et al ., ). Tomentella , the genus with the highest richness in the control plots of both tundra types, showed a sharp negative response to increased snow depth, with a significant sixfold decrease in average OTU richness and a majority of the OTUs disappearing in the dry tundra, as well as an overall decrease in proportional sequence counts.…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that in our study the interaction between OTU richness and potential species abundance likely are habitat‐specific, and are in agreement with studies that addressed species‐species interactions (Kennedy et al ., ; Simard et al ., ; Fransson et al ., ). Collectively, our findings reflect the complexity of arctic tundra responses to predicted changes in summer and winter climate and the need to undertake comparative studies that include multiple ecosystem types even at reduced spatial scales (Welker et al ., ; Walker et al ., ; Sullivan et al ., ,b; Rogers et al ., ; Christensen et al ., ; Leffler & Welker, ; Sharp et al ., ; Lupascu et al ., ). Tomentella , the genus with the highest richness in the control plots of both tundra types, showed a sharp negative response to increased snow depth, with a significant sixfold decrease in average OTU richness and a majority of the OTUs disappearing in the dry tundra, as well as an overall decrease in proportional sequence counts.…”
Section: Discussionmentioning
confidence: 97%
“…Other Arctic snowfence studies have reported contrasting effects of deepened snow on growing season CO 2 exchange (Lupascu, Welker, Xu, & Czimczik, ; Natali et al., ; Rogers, Sullivan, & Welker, ; Semenchuk et al., ). Overall, studies reporting enhanced summertime R eco generally also observed increased plant productivity and soil temperature, moisture, and/or thaw depth, indicating that a combination of enhanced autotrophic and heterotrophic respiration rates contributed to R eco (Natali et al., ; Rogers et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…Low temperatures in Arctic ecosystems limit soil C availability and decomposability (Conant et al, 2011;Davidson and Janssens, 2006). However, global-warming-induced permafrost thaw may partially alleviate this temperature limitation, potentially releasing large amounts of C into the atmosphere via SOM decomposition and further increasing the rate of global warming (Lupascu et al, 2013(Lupascu et al, , 2014aLützow and Kögel-Knabner, 2009;Schuur et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The production of enzymes for the degradation of complex polysaccharides is energetically demanding. Therefore, in an energy-and nutrient-limited ecosystem such as the Arctic tundra (Hobbie et al, 2002;Jonasson et al, 1999;Mack et al, 2004;Chapin III, 1980, 1986;Sistla et al, 2012), more labile substrates are likely preferable, which may lead to accumulation of SOM and thus SOC (Lupascu et al, 2013(Lupascu et al, , 2014a.…”
Section: Functional Shiftsmentioning
confidence: 99%